Pengaruh Penggunaan Cadar Terhadap Kondisi Psikologis Mahasiswi Fakultas Ushuluddin Dan Studi Islam Universitas Islam Negeri Sumatera Utara - Sri Mukhti (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
The use of the veil in the University of North Sumatra, especially the Faculty of Ushuluddin and Islamic Studies, including if an event that has occurred in Indonesia recently has caused negative stereotypes and stigma in society towards the veil, in psychology this can affect a person's mental condition. This study aims to determine how the effect of the use of levels on the psychological condition of students of the Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra. This research is a field research with an approach approach that produces data in the form of writing and observable behavior from the subject, the type of data collection by means of interviews, observation and documentation. The results showed that the effect of the use of the veil on the psychological condition of the students of the Faculty of Ushuluddin and Islamic Studies was influenced by several factors: first, namely internal factors: those from veiled women, those who used the veil with an understanding and guided by religion as a solution in overcoming the negative stigma of society. Second, namely external factors: namely the response or treatment of veil users including negative stigmas against the veil